2009
DOI: 10.1111/j.1945-1474.2009.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Catheter-Associated Urinary Tract Infections

Abstract: This article is the second in a two-part series focusing on catheter-associated urinary tract infections. Part I of the series focused on the most significant modifiable risk factor, avoiding use of urethral catheters. Part II focuses on the second major modifiable risk factor, reducing catheter-days. A quality improvement case is provided to illustrate the strategies for limiting the duration of catheter use. Together, these two articles provide important information on the two most significant risk facts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Urinary tract infections (UTIs) are one of the leading hospital acquired infections, [3][4][5] they can be life-threatening and may lead to increased morbidity, length of hospitalization, and highly affects the costs of healthcare. [1][2][3] It is believed that urinary instrumentation, primarily urinary catheterization, is responsible for nearly 80% of the infections, defined as catheter-associated urinary tract infection (CAUTI).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urinary tract infections (UTIs) are one of the leading hospital acquired infections, [3][4][5] they can be life-threatening and may lead to increased morbidity, length of hospitalization, and highly affects the costs of healthcare. [1][2][3] It is believed that urinary instrumentation, primarily urinary catheterization, is responsible for nearly 80% of the infections, defined as catheter-associated urinary tract infection (CAUTI).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the poor quality of documentation, healthcare staff is often unaware of the insertion and ongoing care of urinary catheters, so that catheters remain in place of excessive lengths of time, until catheter-related complications occur. 5,[10][11][12][13] Studies have indicated that many catheterizations were found as unnecessary and efforts to limit the procedure has been a viable solution. 14,15 Although many surgeons may believe that catheterization is a standard part of some operations, many patients consider it an invasive procedure 12 ; moreover, it is considered to be a painful and uncomfortable procedure even among females, who are believed to experience less CA pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies revealed a statistically signiicant decrease in both catheter-days and incidence of CAUTIs with the implementation of any protocol to increase awareness of the need to remove IUCs. The remaining studies revealed a decrease in CAUTIs that was not statistically signiicant [27,30].…”
Section: Remembering the Forgoten Iuc (Quality Improvement)mentioning
confidence: 99%
“…With the introduction of this concept of "never events," the onus was placed on individual institutions to bear the cost of managing these conditions [27]. With CAUTIs estimated the inancial impact of 27 million US dollars in 2009 in the United States alone [28], this policy provides a signiicant inancial incentive for facilities to develop and support practices to limit the incidence of CAUTIs.…”
Section: Remembering the Forgoten Iuc (Quality Improvement)mentioning
confidence: 99%